Shapley-based risk rankings: some theoretical considerations - Tobias Hiller (International Review of Economics, 2023)
In this note, we enhance the analysis done by Auer and Hiller (Int J Finance Econ 24(2):884–889, 2019; Manag Decis Econ 42(4):876–884, 2021). Whereas their articles uses several simulation settings to illustrate that cooperative game theory may have the potential to solve the low-risk puzzle, we calculate for the three-asset case the conditions for partial ranking corrections between assets. Hence, our note could be interpreted as theoretical counterpart to Auer and Hiller (Int J Finance Econ 24(2):884–889, 2019; Manag Decis Econ 42(4):876–884, 2021).
Keywords: C71; G10; G11; 330; Low-risk puzzle; Cooperative game theory; Shapley value